Dekonstruksi Tokoh Hasan El-Dahsan Dalam Cerpen Si Malang Karya Najib Mahfudz - Halim, Mustabir (Universitas Muhammadiyah Gorontalo, 2024)
The material object in this research is one of Najib Mahfudz's collection of stories with the title